The importance of incorporating an academic advising program in the student services unit at the Foreign Language Department of the University of El Salvador - Castillo Yanez, Ana Milagro
In El Salvador, the learning of English and French as foreign languages have increased more and more in the last years. Nowadays, these languages have become a necessity at the moment of acquiring a job inside or outside the country. However, at the moment of the learning process of any of these foreign languages students face many obstacles such as: lack of advising before entering at the university, misinformation about administrative processes at the beginning, during and at the end of the majors, absence of academic guidance when encountering difficulties to pass a subject, among others. This project will be focused on the importance of incorporating an AAP (Academic Advising program) in the Student Services Unit at the Foreign Language Department, furthermore the benefits that the students of this department will obtain from the implementation of this program.